2006
DOI: 10.1158/0008-5472.can-06-0991
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Detection of p53 Mutations in Plasma DNA from Tobacco Smokers

Abstract: In lung tumors, the p53 tumor suppressor gene is commonly mutated with a characteristic mutation spectrum. The amount of and alterations in plasma DNA, such as mutations in p53, were associated with several cancers. Few studies used quantitative methods of high sensitivity. Previously, we observed p53 mutations in the noncancerous tissue that differed from those in lung tumors using the highly sensitive p53 mutation load assay. Based on our observation of an increased p53 mutation load in nontumorous lung tiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Some authors use small volumes of elution buffer (50碌l) to obtain a concentrated DNA solution for subsequent PCR analysis [24,26]. However, we found that using low volumes of elution buffer led to a significantly lower DNA yield.…”
Section: Discussionmentioning
confidence: 76%
“…Some authors use small volumes of elution buffer (50碌l) to obtain a concentrated DNA solution for subsequent PCR analysis [24,26]. However, we found that using low volumes of elution buffer led to a significantly lower DNA yield.…”
Section: Discussionmentioning
confidence: 76%
“…This is however not the only instance where mutations are detectable in blood samples of healthy individuals. In heavy smokers, mutations known to be induced by tobacco carcinogens are detected in CFDNA even in the absence of any de藛ned lung pathology (51). In a prospective study on cancer risk in a cohort of neversmokers, we have shown that mutations in TP53 and in KRAS could be detected in CFDNA up to several years ahead of diagnosis of speci藛c cancers including bladder cancer (52).…”
Section: Discussionmentioning
confidence: 86%
“…Their findings provided direct evidence for the presence of tumour-derived DNA in the circulation of cancer patients. Recently, studies have also reported that tumour-associated mutations could be found in the plasma/serum of individuals exposed to carcinogens, and the presence of such mutations in the circulation may indicate increased risk of developing cancers (Gormally et al, 2006;Hagiwara et al, 2006). Through the detection of common p53 mutations at codons 273, 249 and 248, Hagiwara et al (2006) reported that p53 mutations were readily detectable in the plasma of some smokers without cancer but not in the plasma of non-smokers.…”
Section: Tumour-associated Mutationsmentioning
confidence: 99%
“…However, the design of allele-specific primers requires the sequence information of the mutation, which can only be obtained when the primary tumour tissue is available. Alternatively, hotspot-mutations, for example mutations at codons 248 and 249 of the p53 gene and mutations at the codon 12 of the KRAS gene, can be screened for in the plasma (Gormally et al, 2006;Hagiwara et al, 2006). However, this approach would miss the tumour-associated mutations occurring outside the mutation hot spots and, hence, might reduce the sensitivity of the test.…”
Section: Tumour-associated Mutationsmentioning
confidence: 99%